A SEMANTIC AND PRAGMATIC ANALYSIS OF TOURISM ADVERTISING: TOURIST LEAFLETS FROM SIBIU - NEGOESCU, Alina Gabriela (2014)
Tourism is one of the most important industries of the world economy, having a great contribution to economical development. In tourism, where the product is ‘intangible’ (there is nothing tangible for tourists to test in advance), ‘inseparable’ (services cannot be separated from their production), ‘variable’ (the experience is variable and subject to multiple factors) and ‘perishable’ (tourism product is perishable and cannot be stored for future sale), advertising has a vital role. People buy a holiday on the basis of certain symbolic expectations created by advertisers through words, pictures, sounds, etc. Thus, advertising constructs tourism experiences in our imagination and makes an intangible product tangible, using emotions and experiences. Since tourists do not know what to expect, advertising offers them physical representations of the tourism product.